2022
DOI: 10.1038/s41598-022-23086-z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on shear characteristics of the silty clay soil-ice interface

Abstract: During the spring thawing, the decrease of soil-ice interface strength by temperature may lead to slope instability. For this reason, some researchers have explored the relationship between temperature and soil-ice interface strength. However, previous studies have not systematically explored the change law of strength at the soil-ice interface from negative temperature to 0 °C. Therefore, direct shear tests were conducted at different shear temperatures and different moisture contents. The effects of temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…For Hamelin Creek (Alberta), slope stability analyses were conducted by varying soil properties and no water table. For the partially frozen soil, the shear parameters (c = 40 kPa and  = 30°) were based on a similar soil (Huang et al, 2022). The FOS was found to be 0.98 for c = 6 kPa and  = 18° thereby validating the analysis of Tweedie et al (2004).…”
Section: Analysis and Discussionsupporting
confidence: 73%
“…For Hamelin Creek (Alberta), slope stability analyses were conducted by varying soil properties and no water table. For the partially frozen soil, the shear parameters (c = 40 kPa and  = 30°) were based on a similar soil (Huang et al, 2022). The FOS was found to be 0.98 for c = 6 kPa and  = 18° thereby validating the analysis of Tweedie et al (2004).…”
Section: Analysis and Discussionsupporting
confidence: 73%
“…The parameters η1, η2, η3, and η4 are shown in Table 5. Note that the friction angle decreases as the temperature drops from −1 °C to −2 °C; the same conclusion has been reached in the studies of the frozen silty soil-structure interface [45,46]. The ice crystals fill the pores in the soil near the interface, and the roughness of the interface is reduced by the formation of ice aggregates.…”
Section: Variation Of the Peak Shear Stress With The Number Of Cycles...supporting
confidence: 71%
“…The image of the specimen surface after testing also confirmed the existence of ice aggregates on the interface (Figure 11). On the contrary, Huang et al [45] and Shi et al [47] studied the ice-soil interface, and they found that the friction angle increases with decreasing temperature. The formation mechanism of the friction angle of the two interfaces is different.…”
Section: Variation Of the Peak Shear Stress With The Number Of Cycles...mentioning
confidence: 98%
See 1 more Smart Citation
“…Noroozi, A. G et al [23] conducted a series of tests to study the shear characteristic of the soil-concrete interface. Huang et al [24] investigated the effect of temperature on the shear properties of the soil-ice interface through low-temperature shear tests.…”
Section: Introductionmentioning
confidence: 99%